'Virtual experience' as an intervention before a positron emission tomography/CT scan may ease patients' anxiety and improve image quality. Issue 5 (30th June 2020) - Sun, Yuyun; Sun, Yifei; Qin, Yue; Zhang, Yingjian; Yuan, Huiyu; Yang, Zhongyi
Abstract: Introduction: The aim of our study was to investigate the effect of a 'virtual experience' on reducing people's anxiety levels and improving image quality. Methods: This study included 200 people who underwent 18 F‐FDG PET/CT scan for the first time. Healthy people ( n  = 100) and patients ( n  = 100) were randomly divided into a control group and an intervention group. In the intervention group, we used a 'virtual experience' as an intervention before the scan. We used the Spielberger State‐Trait Anxiety Inventory (STAI) and satisfaction questionnaires for evaluation. Additionally, the image quality was analysed. Results: In the control group, more patients presented anxiety than healthy people (26(52%) versus 15(30%)) ( P  = 0.041). However, when the 'virtual experience' was provided, the number of cases of anxiety in the patient group decreased to 19(38%). Furthermore, patients in the intervention group had lower STAI‐related scores than those in the control group (STAI‐S: 37.08 ± 9.42 versus 43.34 ± 10.49, P  = 0.109; STAI‐T: 36.24 ± 9.55 versus 40.72 ± 9.00, P  = 0.019). With respect to image quality, people who had higher STAI‐related scores were more likely to have unqualified images. Conclusion: A 'virtual experience' provided by an audio‐visual installation can ease patients' anxiety and improve image quality.